(untitled) (Bangladesh Critical Care Journal, 2015)
Background and Aims: Data on Bacterial isolates from tracheal aspirates in children with severe pneumonia requiring intubation and mechanical ventilation especially in developing countries are very limited. We examined the microbial spectrum of bacteria isolated from tracheal aspirate of those children. The antibiotic susceptibility profiles of those bacteria were also examined. Methods: We evaluated the data of all mechanically ventilated children aged 0-59 months admitted to Intensive Care Unit (ICU) of Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) between August 2009 and July 2013 having their tracheal aspirate culture done. Data were extracted from electronic medical records of the Dhaka Hospital. Results: Among 836 admitted pneumonia children in the ICU, we identified 35 children who fulfilled the inclusion criteria. Among them 34 (97%) had positive bacterial growths: Klebseilla species in 14 (40%), Escherichia coli in 11 (31%), Acinetobacter in 8 (23%) and Streptococcus species in 8 (23%). Additionally, Enterococcus, Staphylococcus aureus, Pseudominas and Proteus species were identified in 6 (17%), 4 (11%), and 2 (6%) of the children respectively. The susceptibility of the gram-negatives, except Klebseilla, to ampicillin, cotrimoxazole, gentamycin, ciprofloxacin, azithromycin, and ceftriaxone ranged from 0- 54%, while that for ceftazidime and amikacin ranged from 12-80%. The sensitivity of Klebseilla to these antibiotics ranged from 0-100%. Conclusions: Our data suggests that gram-negative bacteria, Klebseilla followed by Escherichia coli, and Acenetobacter are the predominant bacteria associated with severe pneumonia in ventilated children. The increased number of infections caused by Gram-negative bacteria is being accompanied by rising rates of multi-drug resistance which underscores the importance of aggressive antimicrobial therapy in the management of such children. Bangladesh Crit Care J September 2014; 2 (2): 60-64